2009
DOI: 10.1177/230949900901700213
|View full text |Cite
|
Sign up to set email alerts
|

Low Back Pain and Cervical Spondylotic Myelopathy

Abstract: In some patients, low back pain may be improved following cervical laminoplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 6 publications
0
13
1
Order By: Relevance
“…In the present study, the outcome of surgery where 28% of patients showed significant improvement in their symptoms, while 52% showed slight improvement. No improvement was seen in 20% of patients, whereas no deterioration in symptoms noted in any of patients in this study compared with the Kawakita et al and Benzel studies (12,13) . The course of the lesion may be slow and prolonged, and the patients may either remain asymptomatic or have mild cervical pain, long periods of non-progressive disability are typical, and in a few cases, the patient's condition progressively deteriorated.…”
Section: Resultscontrasting
confidence: 54%
“…In the present study, the outcome of surgery where 28% of patients showed significant improvement in their symptoms, while 52% showed slight improvement. No improvement was seen in 20% of patients, whereas no deterioration in symptoms noted in any of patients in this study compared with the Kawakita et al and Benzel studies (12,13) . The course of the lesion may be slow and prolonged, and the patients may either remain asymptomatic or have mild cervical pain, long periods of non-progressive disability are typical, and in a few cases, the patient's condition progressively deteriorated.…”
Section: Resultscontrasting
confidence: 54%
“…Cervical myelopathy surgery occasionally provides long-term relief of LBP. [38][39][40] Accordingly, cervical decompression preceding lumbar surgery may be beneficial for patients with tandem spinal stenosis presenting primarily with LBP. However, treatment targets are difficult to identify because the clinical features of cervical pathology-related LBP remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, cervical myelopathy may also cause non-dermatomal extremity pain or even low back pain, known as a false-localising sign, as was present in case 2. Although the mechanism of this phenomena has not been fully established, it is proposed to result from a disorder of the spinothalamic tract 24 25…”
Section: Discussionmentioning
confidence: 99%